Controlled Comparison of Original Vented Aerobic FAN Medium with New Nonvented BacT/ALERT FA Medium for Culturing Blood - Mirrett, Stanley (American Society for Microbiology, 2001)
To evaluate the performance of BacT/ALERT FA (FA) medium, a new aerobic BacT/ALERT FAN (FAN) medium (Organon Teknika Corporation, Durham, N.C.) that does not require the added cost and inconvenience of a venting unit, we inoculated blood specimens from adult patients with suspected sepsis into an original FAN aerobic culture bottle and an FA bottle. Of 7,745 blood culture sets containing both bottles, 5,256 (68%) met the criteria for adequacy of filling. A total of 466 isolates judged to represent the causes of true infections were recovered from 276 patients; 271 isolates were recovered from both bottles, 82 were recovered from the FAN bottle only, and 113 were recovered from the FA bottle only (P < 0.05). More Burkholderia cepacia isolates (P < 0.01), Candida albicans isolates (P < 0.001), Cryptococcus neoformans isolates (P < 0.01), yeasts overall (P < 0.001), and total microorganisms (P < 0.05) were recovered from FA bottles. Of cultures found to be positive within the first 72 h of incubation, the mean times to detection were almost identical for FAN (20.4 h) and FA (20.7 h) bottles. Of 263 isolates that caused monomicrobic episodes of bloodstream infections, 180 were detected in both bottles, 32 were detected in FAN bottles only, and 51 were detected in FA bottles only (P < 0.05). Of 186 isolates considered to be contaminants, 63 were detected in both media, 64 were detected in FAN bottles only, and 59 were detected in FA bottles only (P was not significant). The number of false-positive results were comparable: 69 (1.3%) in FAN bottles and 56 (1.1%) in FA bottles. However, there were 14 isolates with false-negative results (6 yeasts, 6 nonfermenters, and 1 isolate each of Propionibacterium acnes and coagulase-negative staphylococci) in FAN bottles, whereas there were none in FA bottles. On the basis of these results, we conclude that the new nonvented FA bottle is superior to the original vented FAN medium for the recovery of B. cepacia and yeasts, especially C. albicans and C. neoformans, and is comparable to FAN medium for other microorganisms.